THE CONCEPT OF THE CHILD’S RESIDENCE - Zargaryan, Hayarpi (State and Law, 2022)
In the context of the child’s right to free movement, the child’s right to a place of residence is exercised, which, as an independent right but an integral part of the right to free movement, needs to be defined and enshrined in law. A study of domestic legal acts shows that they do not define the concept of a person’s place of residence, moreover, there is no definition of "place of residence of a child". It is not provided by the legislation of the Republic of Armenia, and the study of the case law shows that the phrase "place of residence of the child" is not clearly understood. This article proposes to make an addition to the RA Law on the Rights of the Child, that is, to supplement Chapter II entitled "Fundamental Rights of the Child - Their Guarantees" with a separate article entitled "Place of residence of the child".